Whole Genome Amplification of DNA for Genotyping Pharmacogenetics Candidate Genes - Philips, Santosh; Rae, James M.; Oesterreich, Steffi; Hayes, Daniel F.; Stearns, Vered; Henry, Norah L.; Storniolo, Anna M.; Flockhart, David A.; Skaar, Todd C. (Frontiers in Pharmacology, 2012)
Whole genome amplification (WGA) technologies can be used to amplify genomic DNA when only small amounts of DNA are available. The Multiple Displacement Amplification Phi polymerase based amplification has been shown to accurately amplify DNA for a variety of genotyping assays; however, it has not been tested for genotyping many of the clinically relevant genes important for pharmacogenetic studies, such as the cytochrome P450 genes, that are typically difficult to genotype due to multiple pseudogenes, copy number variations, and high similarity to other related genes. We evaluated whole genome amplified samples for Taqman™ genotyping of SNPs in a variety of pharmacogenetic genes. In 24 DNA samples from the Coriell human diversity panel, the call rates and concordance between amplified (~200-fold amplification) and unamplified samples was 100% for two SNPs in CYP2D6 and one in ESR1. In samples from a breast cancer clinical trial (Trial 1), we compared the genotyping results in samples before and after WGA for four SNPs in CYP2D6, one SNP in CYP2C19, one SNP in CYP19A1, two SNPs in ESR1, and two SNPs in ESR2. The concordance rates were all >97%. Finally, we compared the allele frequencies of 143 SNPs determined in Trial 1 (whole genome amplified DNA) to the allele frequencies determined in unamplified DNA samples from a separate trial (Trial 2) that enrolled a similar population. The call rates and allele frequencies between the two trials were 98% and 99.7%, respectively. We conclude that the whole genome amplified DNA is suitable for Taqman™ genotyping for a wide variety of pharmacogenetically relevant SNPs.